Kinetics and dynamics of ivermectin removal from sheep organism after using iverlong - E. S. Engasheva; S. V. Rusakov (Российский паразитологический журнал, 2016)
The pharmacokinetics and dynamics of ivermectin removal from sheep organism is studied. Iverlong contains in sheep organism at level below a limit of detecting of the method.